The FASB Conceptual Framework 1973-1985: An Analysis. - Ayres, Frances L.; Moriarity, Shane R. (The Accounting Review, 1993)
Reviews the book "The FASB Conceptual Framework 1973-1985: An Analysis," by Pelham Gore.